Effectiveness and efficiency of virtual reality designs to enhance athlete development: an ecological dynamics perspective - Stone, J. A.; Strafford, B. W.; North, J. S.; Toner, C.; Davids, K. (Movement & Sport Sciences - Science & Motricité, 2018)
A rapidly developing area of research is focused on the use of virtual reality (VR) systems to enhance athlete performance in sport. The assumption is that, implementation of such technologies will enhance skill acquisition and expedite athlete development. However, application of such technologies for enriching athlete development and performance preparation needs to be efficiently and effectively used by coaches and athletes to save time, energy and other resources in practice and training. Here, we argue that implementation of VR systems needs to be grounded in theory, with learning designs informed by a clear scientific rationale. We discuss how the full potential of VR systems can be utilised through implementing a theoretical framework, like ecological dynamics, to shape their application. We outline how an ecological dynamics framework can underpin research and applications of VR in athlete development through: (i) individualised training and assessment programmes; (ii) supporting exploration of variable and creative practice environments; (iii) ensuring context-dependent perception and decision making, and actions, where technology permits. An ecological dynamics rationale proposes how VR systems, when carefully implemented, can enrich and enhance learning designs, but can never replace coaching support for learning during physical practice.